Cardiac work is related to creatine kinase energy supply in human heart failure: a cardiovascular magnetic resonance spectroscopy study - Gabr, Refaat E.; El-Sharkawy, AbdEl-Monem M.; Schär, Michael; Panjrath, Gurusher S.; Gerstenblith, Gary; Weiss, Robert G.; Bottomley, Paul A. (Journal of cardiovascular magnetic resonance, 2018)
It has been hypothesized that the supply of chemical energy may be insufficient to fuel normal mechanical pump function in heart failure (HF). The creatine kinase (CK) reaction serves as the heart's primary energy reserve, and the supply of adenosine triphosphate (ATP flux) it provides is reduced in human HF. However, the relationship between the CK energy supply and the mechanical energy expended has never been quantified in the human heart. This study tests whether reduced CK energy supply is associated with reduced mechanical work in HF patients. Cardiac mechanical work and CK flux in W/kg, and mechanical efficiency were measured noninvasively at rest using cardiac pressure-volume loops, magnetic resonance imaging and phosphorus spectroscopy in 14 healthy subjects and 27 patients with mild-to-moderate HF. In HF, the resting CK flux (126 ± 46 vs. 179 ± 50 W/kg, p < 0.002), the average (6.8 ± 3.1 vs. 10.1 ± 1.5 W/kg, p  <0.001) and the peak (32 ± 14 vs. 48 ± 8 W/kg, p < 0.001) cardiac mechanical work-rates, as well as the cardiac mechanical efficiency (53% ± 16 vs. 79% ± 3, p < 0.001), were all reduced by a third compared to healthy subjects. In addition, cardiac CK flux correlated with the resting peak and average mechanical power (p < 0.01), and with mechanical efficiency (p = 0.002). These first noninvasive findings showing that cardiac mechanical work and efficiency in mild-to-moderate human HF decrease proportionately with CK ATP energy supply, are consistent with the energy deprivation hypothesis of HF. CK energy supply exceeds mechanical work at rest but lies within a range that may be limiting with moderate activity, and thus presents a promising target for HF treatment. ClinicalTrials.gov Identifier: NCT00181259 .